Water-based environment-friendly strippable coating for glass substrate and preparation method thereof

By chemically modifying PDMS and covalently bonding it to the acrylic resin molecular chain, the compatibility problem of water-based peelable coatings on glass substrates was solved, resulting in a coating with high cohesive strength, easy peeling, and heat resistance, suitable for temporary protection and demolding of glass substrates.

CN121699462APending Publication Date: 2026-03-20ZHEJIANG JINGGONG SCI & TECH

Patent Information

Application Number
CN202511894484.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-16
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

Existing water-based peelable coatings have compatibility issues on glass substrates, resulting in high coating brittleness, insufficient cohesion, difficulty in achieving complete removal over large areas, and limited heat resistance, making them unsuitable for stable use in high-temperature environments.

Method used

By chemically modifying PDMS to obtain reactive functional groups that can participate in free radical polymerization, it is then covalently bonded to the acrylic resin molecular chain through in-situ emulsion polymerization to form a stable polymer alloy or interpenetrating network structure.

Benefits of technology

It achieves uniform adhesion and easy peeling of the coating on glass substrates, while also possessing high cohesive strength and toughness, improved heat resistance, and being environmentally friendly with no VOCs, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a water-based environment-friendly peelable coating for a glass substrate and a preparation method of the water-based environment-friendly peelable coating, and belongs to the technical field of water-based coatings. The preparation method comprises the following steps: firstly, carrying out chemical modification on polydimethylsiloxane (PDMS) by utilizing a silane coupling agent to prepare K-PDMS with polymerizable double bonds; then carrying out copolymerization on the K-PDMS and an acrylate monomer through an emulsion polymerization method to prepare a water-based acrylic resin emulsion; and finally, mixing the emulsion with deionized water, an auxiliary agent and color paste to prepare a water-based strippable coating, applying the water-based strippable coating to the surface of a glass substrate, and drying to form a strippable coating. According to the present invention, the compatibility problem of PDMS and acrylic resin is fundamentally solved through the chemical bonding manner, such that the obtained coating has advantages of excellent peelability, high mechanical strength, prominent hydrophobicity and good heat resistance, and is especially suitable for the efficient demolding of the glass mold and the temporary surface protection of the glass product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of fine chemicals and polymer materials technology, and in particular to a water-based environmentally friendly peelable coating for glass substrates and its preparation method. Background Technology

[0002] In fields such as composite material manufacturing, precision instrument transportation, electronic product processing, and architectural decoration, there is often a need for temporary protection of specific surfaces or to provide easily removable release layers. Traditionally, solvent-based peelable coatings have been widely used due to their good film-forming properties and peeling effects. However, these coatings release large amounts of volatile organic compounds (VOCs) during production and use, posing a serious threat to the environment and the health of operators, and also creating fire safety hazards. With increasingly stringent global environmental regulations, the development of low-VOC, environmentally friendly water-based peelable coatings has become an inevitable trend.

[0003] However, applying water-based systems to peelable coatings, especially to high-surface-energy, smooth, and chemically stable substrates like glass, faces a series of technical bottlenecks. First, to achieve "peelability," the coating needs to possess "moderate adhesion": it cannot be too weak, leading to premature peeling, nor too strong, making removal difficult. Existing water-based peelable coatings often achieve this through designing low cross-linking degrees or high elastomer content, but this often comes at the cost of sacrificing the coating's mechanical strength, resulting in a brittle film, insufficient cohesion, and easy fragmentation during peeling, making large-area complete removal impossible (see the film brittleness issue mentioned in CN108472920B). Second, glass molds often undergo temperature cycling (e.g., from room temperature to above 120°C) in composite material molding processes. Ordinary water-based acrylic coatings have limited heat resistance and are prone to becoming sticky, softening, or brittle and cracking at high temperatures, losing their protective or demolding function.

[0004] Polydimethylsiloxane (PDMS) is considered an ideal additive for enhancing the aforementioned properties due to its extremely low surface tension (~20 mN / m), excellent flexibility, wide temperature range (-50℃ to 200℃), and outstanding hydrophobicity. Introducing it into coatings is expected to reduce surface energy (facilitating peeling), enhance toughness, and improve heat resistance. However, PDMS has extremely poor compatibility with highly polar waterborne acrylic resins; the surface energy difference between the two is enormous, and simple physical blending leads to severe macroscopic phase separation. Existing technologies have attempted methods such as post-blending PDMS as a separate additive or physical blending using PDMS emulsions, but these methods only result in weak physical adsorption or mechanical interlocking between PDMS and the resin matrix. During film formation, use, or temperature changes, PDMS is prone to migration, aggregation, and even precipitation (i.e., "oil separation"). This not only fails to stably utilize the performance advantages of PDMS but also leads to a sticky coating surface, uneven strength, poor long-term stability, and even the formation of weak points at the interface, deteriorating peeling performance.

[0005] Therefore, there is an urgent need in this field for an innovative technical solution that can fundamentally solve the compatibility problem between PDMS and waterborne acrylic resin, thereby preparing a waterborne peelable coating specifically for glass substrates. The coating should simultaneously meet the following comprehensive performance requirements: (1) Environmental protection: water is the main dispersion medium, and the VOC content is low; (2) Peelability: the adhesion on the glass surface is uniform and moderate, and it can easily achieve large-area complete peeling without residue; (3) Mechanical properties: it has sufficient toughness and tensile strength, and is not easy to break during peeling; (4) Temperature resistance: it can withstand certain high temperature environments (such as ≥120℃) and high and low temperature cycles, and its performance is stable; (5) Process stability: the preparation process is mature and controllable, the resulting product is stable in storage, and it is suitable for industrial production and application. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a novel technical solution for the stable introduction of PDMS into an aqueous acrylic resin system through chemical bonding, specifically in three aspects: product, method, and application.

[0007] In a first aspect, the present invention provides a method for preparing a water-based, environmentally friendly, peelable coating.

[0008] The core feature of this method is that PDMS is first chemically modified to acquire reactive functional groups capable of participating in free radical polymerization, and then covalently bonded to the acrylic resin molecular chain via in-situ emulsion polymerization. Specifically, it includes the following steps: (1) Preparation of reactive PDMS (K-PDMS): Under an inert atmosphere, terminal hydroxyl or hydrogen-terminated polydimethylsiloxane (PDMS) is grafted or capped with a silane coupling agent containing unsaturated double bonds in the presence of an organic solvent and a catalyst. After the reaction is complete, the solvent is removed to obtain modified PDMS with polymerizable double bonds such as (meth)acryloyloxy groups on the molecular chain, denoted as K-PDMS. This step is a key prerequisite for solving compatibility issues.

[0009] (2) Preparation of pre-emulsion: The emulsifier is dissolved in a portion of deionized water, and the mixture of (meth)acrylate monomers and the K-PDMS prepared in step (1) are added sequentially under appropriate stirring speed to form a uniform and stable oil / water pre-emulsion. Here, K-PDMS participates in the emulsification process as a functional macromonomer.

[0010] (3) Seed emulsion polymerization: Add the remaining deionized water and buffer to the reactor and heat to 75-85℃. First, add a portion (e.g., 40%-60%) of the pre-emulsion obtained in step (2), and then add a small portion (e.g., 5%-10% of the total mass) of water-soluble free radical initiator solution. After initiating polymerization, the system exhibits a distinct "blue light" phenomenon, forming a stable seed emulsion.

[0011] (4) Semi-continuous dropwise polymerization and ripening: Maintaining the reaction temperature, the remaining pre-emulsion and initiator solution are simultaneously and uniformly added to the seed emulsion via a constant flow pump over 1-3 hours. After the addition is complete, the temperature is raised to 85-95℃ and maintained for ripening for 0.5-2 hours to allow the monomers to fully convert and obtain a stable waterborne acrylic resin emulsion. During this process, the double bonds on K-PDMS undergo copolymerization with the acrylate monomers to form chemical bonds.

[0012] (5) Emulsion post-treatment: Cool the polymer emulsion to below 40°C and neutralize the pH of the system to 6-8 with an alkaline pH adjuster (such as ammonia or organic amine) to stabilize the carboxyl groups in the emulsion and improve storage stability. Finally, remove any possible gel particles by filtration (such as a 200-400 mesh filter) to obtain the final aqueous acrylic resin emulsion.

[0013] (6) Coating preparation: The water-based acrylic resin emulsion obtained in step (5) is mixed with deionized water, and at least two additives selected from defoamers, wetting agents, leveling agents, thickeners, dispersants, and color paste (if required) in proportion, and dispersed at high speed to obtain an instant water-based environmentally friendly peelable coating. The coating is applied to the surface of a cleaned glass substrate by spraying, brushing, or dipping, and dried at 60-100℃ to form a film, thus forming the peelable coating.

[0014] Preferably, in step (1), the silane coupling agent containing unsaturated double bonds is γ-(methacryloyloxy)propyltrimethoxysilane (KH570). The organic solvent is preferably 2-methyltetrahydrofuran, toluene, or tetrahydrofuran. The catalyst is preferably a tin-based catalyst, such as dibutyltin dilaurate. The molar ratio of PDMS to the silane coupling agent is preferably between 1:0.8 and 1:1.2, the reaction temperature is preferably 50-70°C, and the reaction time is 4-6 hours.

[0015] Preferably, in step (2), the amount of the acrylate monomers used is 80-100 parts by weight, and the amount of K-PDMS used is 1-10 parts by weight, based on the total mass of the reactants. The total amount of emulsifier used is 2%-6% of the total mass of the monomers and K-PDMS. The acrylate monomers include hard monomers (such as methyl methacrylate and styrene), soft monomers (such as butyl acrylate and isooctyl acrylate), and functional monomers (such as acrylic acid, methacrylic acid, and hydroxyethyl (meth)acrylate). The glass transition temperature (Tg), flexibility, and adhesion of the coating can be controlled by adjusting their proportions.

[0016] More preferably, in step (2), the emulsifier is a compound system comprising a nonionic emulsifier (such as alkylphenol polyoxyethylene ether OP-10, octylphenol polyoxyethylene ether TX-10) and an anionic emulsifier (such as sodium dodecyl sulfate SDS, sodium dodecylbenzene sulfonate SDBS), with the mass ratio of the two preferably between (1:1) and (3:1). The compound emulsifier can synergistically stabilize the emulsion system containing hydrophobic K-PDMS.

[0017] Preferably, in steps (3) and (4), the buffer is sodium bicarbonate or ammonium bicarbonate, used to maintain the pH stability of the reaction system. The initiator is a water-soluble persulfate, such as ammonium persulfate or potassium persulfate.

[0018] Preferably, in step (3), the amount of the pre-emulsion is 40%-60% of the total amount of the pre-emulsion; and the amount of the initiator is 5%-10% of the total mass of the initiator.

[0019] Preferably, in step (5), ammonia or organic amines are used as pH adjusters.

[0020] Preferably, in step (6), the additives include at least two of the following: defoamer, wetting agent, leveling agent, thickener, and dispersant; the amount of the water-based acrylic resin emulsion used is 60-80 parts by weight based on the total mass of the coating. The additives are water-based coating additives.

[0021] Secondly, this invention provides a water-based, environmentally friendly, peelable coating. This coating is prepared by mixing a water-based acrylic resin emulsion obtained by any of the preparation methods described in the first aspect as the core film-forming substance, with deionized water, additives, and colorant (added according to the desired color) in a certain proportion. The additives include, but are not limited to, at least two of defoamers, wetting agents, leveling agents, thickeners, and dispersants, used to improve the coating's application performance, stability, and final film appearance. This coating is a water-based system, environmentally friendly, with low VOC content, stable in storage, and can be used directly in application.

[0022] Thirdly, the present invention provides a water-based, environmentally friendly, peelable coating for a glass substrate. This coating is formed by applying the water-based, environmentally friendly, peelable coating described in the second aspect above to the surface of a clean glass substrate via spraying, brushing, or dipping, and then drying. The coating exhibits moderate and uniform adhesion to the glass substrate, ensuring both effective temporary adhesion and easy removal when needed.

[0023] Preferably, the coating exhibits the following outstanding overall properties: Excellent hydrophobicity and easy peelability: The water contact angle of the coating is ≥90°. More preferably, the contact angle is ≥102°, which indicates that the coating surface has extremely low surface energy, which helps to achieve smooth and complete peeling and has anti-fouling effect.

[0024] High mechanical strength and toughness: The tensile strength of the coating film is ≥12MPa. More preferably, the tensile strength is ≥13MPa, which gives the coating sufficient cohesive strength and toughness, making it less prone to tearing or breaking during peeling and use, and enabling large-area whole-piece peeling.

[0025] More preferably, the coating also possesses the following performance characteristics: Suitable hardness: The coating has a pencil hardness in the range of B to HB, providing basic scratch resistance and meeting the requirements for temporary protection.

[0026] Good thermal stability: The thermal decomposition temperature of the coating is ≥260℃, indicating that it has good thermal stability and can withstand a certain degree of short-term heat exposure (e.g. in mold making) without performance degradation.

[0027] Furthermore, the present invention provides a method for demolding protection of glass molds.

[0028] This method utilizes the coatings and coatings provided by the present invention, and specifically includes the following steps: (1) Clean the surface of the glass mold; (2) Apply the water-based environmentally friendly peelable coating described in the second aspect above to the treated mold surface; (3) After drying, a peelable coating with excellent properties as described in the third aspect above is formed on the surface of the mold; (4) Subsequent product molding processes (such as composite material lay-up, resin injection or molding) are carried out on the coating. (5) After the product has cured or been formed, the cured product, together with the peelable coating, can be easily and completely peeled off from the glass mold as a whole by simply peeling it off from the edge of the coating. The mold surface is clean and new, and no additional cleaning is required.

[0029] Furthermore, this invention provides applications of the above-mentioned technical solutions in related fields.

[0030] Specifically, the present invention provides applications of the aqueous acrylic resin emulsion prepared by any of the methods described in the first aspect, the aqueous environmentally friendly peelable coating described in the second aspect, or the peelable coating described in the third aspect in the following fields: As an efficient demolding layer for glass molds (especially those with complex shapes or high gloss requirements), it solves demolding problems and protects the mold surface; As a temporary surface protective film for various glass products (such as architectural glass, optical glass, instrument glass, and art glass) during processing, transportation, storage, or installation, it prevents scratches, contamination, or corrosion.

[0031] Compared with existing technologies, this invention achieves the following significant beneficial effects through an innovative "modification first, copolymerization later" strategy: 1. Fundamentally solves the compatibility problem: By chemically modifying PDMS to introduce polymerizable double bonds, it transforms from an "inert additive" into an "active comonomer." In emulsion polymerization, K-PDMS is covalently bonded to the main chain or side chains of acrylic resin, forming a stable polymer alloy or interpenetrating network structure. This ensures that PDMS segments are uniformly and stably dispersed in the resin matrix at the nanoscale or molecular scale, completely avoiding the macroscopic phase separation, migration, and precipitation problems caused by physical blending.

[0032] 2. Through the synergistic effect of chemically bonded PDMS segments and acrylic resin network, precise and synergistic improvement of coating performance is achieved: PDMS endows the coating with excellent flexibility and elasticity, while acrylic resin provides skeletal strength. Together, they enable the coating to maintain moderate adhesion and easy peeling while possessing high cohesive strength and toughness, achieving the effect of "easy peeling without breaking the whole sheet"; chemical bonding effectively transfers the inherent high Si-O bond energy and thermal stability of PDMS to the entire coating system, significantly improving the thermal decomposition temperature and short-term heat resistance, and avoiding performance degradation caused by PDMS migration; at the same time, the bonded PDMS segments accumulate on the surface during film formation, giving the coating durable and outstanding hydrophobicity and low surface energy characteristics, which not only have a large contact angle and good water resistance and antifouling properties, but also further ensure the smoothness of the peeling process.

[0033] 3. High Environmental and Practical Value: The entire technical route uses water as the continuous phase, eliminating the use of large amounts of organic solvents at the source. The VOC content of the product is far below national and international environmental protection standards. The preparation process has clear steps, controllable parameters, and is easy to implement for industrial production. The prepared coating is specifically optimized for glass substrates and performs excellently in solving the problem of demolding glass molds, showing broad market application prospects. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that these embodiments are merely some examples of this invention and are used for illustration rather than limiting the scope of protection of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0035] In the description of the embodiments, it should be understood that all experimental steps, process parameters, raw material ratios, and performance testing methods are provided to better illustrate the technical solution of the present invention and verify its beneficial effects, and are not intended to limit the present invention. Unless otherwise explicitly stated, "parts" in the embodiments refer to parts by weight. Experimental methods in the following embodiments that do not specify specific conditions are generally performed according to conventional conditions in the art or according to the manufacturer's recommendations. Unless otherwise specified, the reagents and raw materials used are all commercially available conventional products. Those skilled in the art can make appropriate adjustments or substitutions to the conditions, steps, and parameters without departing from the concept of the present invention, and such adjustments or substitutions should be considered to fall within the protection scope of the present invention.

[0036] Example 1: Preparation of reactive PDMS (K-PDMS) This embodiment details the preparation process of K-PDMS.

[0037] The raw materials included: 100 g of hydroxyl-terminated polydimethylsiloxane (PDMS, molecular weight approximately 5000 g / mol, viscosity approximately 1000 mPa·s (25℃)), 15 g of γ-(methacryloyloxy)propyltrimethoxysilane (KH570), 150 mL of anhydrous 2-methyltetrahydrofuran (2-MeTHF) as solvent, and 0.8 g of dibutyltin dilaurate (DBTDL) as catalyst. The reaction was carried out under nitrogen protection.

[0038] The equipment used includes a 250mL three-necked flask, a mechanical stirrer, a constant temperature oil bath, a reflux condenser, a thermometer, a nitrogen inlet tube, and a rotary evaporator.

[0039] The preparation steps are as follows: First, the reaction apparatus is assembled and purged with a weak nitrogen stream for about 10 minutes to remove air. Under a nitrogen atmosphere, PDMS and 2-MeTHF are added sequentially to the flask, and stirring is started (about 200 rpm) to ensure complete dissolution. Subsequently, a mixture of KH570 and DBTDL is slowly added to the flask while stirring. After the addition is complete, the oil bath temperature is raised to 60±2℃, and the reaction is continued at this temperature with stirring for 5 hours, while maintaining a weak nitrogen atmosphere. After the reaction is complete, the reaction solution is cooled to room temperature and transferred to a rotary evaporator. The solvent 2-MeTHF is completely removed under reduced pressure (about -0.095 MPa) in an 80℃ water bath, yielding a colorless to pale yellow, transparent, viscous liquid product, which is K-PDMS, weighing approximately 108 grams.

[0040] The product was verified by Fourier transform infrared spectroscopy (FT-IR). Comparison with the PDMS spectrum of the raw material revealed a difference at approximately 1635 cm⁻¹. -1 Approximately 1720cm -1 The appearance of new characteristic absorption peaks nearby, which are attributed to carbon-carbon double bonds (C=C) and ester carbonyl groups (C=O), proves that KH570 has been successfully grafted onto the PDMS chain, introducing polymerizable methacrylate groups.

[0041] Example 2: Preparation of an aqueous acrylic resin emulsion (A1) containing K-PDMS This embodiment illustrates the specific process for preparing aqueous resin emulsions using the aforementioned K-PDMS.

[0042] The raw materials, by weight, are as follows: The pre-emulsification stage includes 150 parts deionized water, 3.0 parts emulsifier OP-10 (alkylphenol polyoxyethylene ether), 1.5 parts emulsifier SDS (sodium dodecyl sulfate), 70 parts methyl methacrylate (MMA), 20 parts butyl acrylate (BA), 3 parts acrylic acid (AA), 2 parts hydroxyethyl methacrylate (HEMA), and 5 parts K-PDMS prepared in Example 1. The polymerization stage includes 100 parts deionized water, 1.0 part buffer sodium bicarbonate (NaHCO3), and 2.0 parts initiator ammonium persulfate (APS) (dissolved in 20 parts deionized water). A suitable amount of 25% ammonia water is used as a pH adjuster in the post-treatment.

[0043] The equipment used includes a 1L four-necked flask (reaction vessel), a mechanical stirrer, a constant temperature water bath, a condenser, two constant pressure dropping funnels, and a thermometer.

[0044] The preparation steps are as follows: First, pre-emulsification is performed. Deionized water, OP-10, and SDS are added to a 500mL beaker and stirred at 300rpm for 5 minutes to dissolve them. Then, MMA, BA, AA, HEMA, and K-PDMS are added slowly in sequence. After the addition is complete, the stirring speed is increased to 800-1000rpm, and high-speed shear emulsification is continued for 30 minutes to obtain a homogeneous pre-emulsion for later use. Then, deionized water and NaHCO3 are added to a reaction vessel and stirred to dissolve them. Then, about 50% of the pre-emulsion (about 128 parts) is added, and stirring is started (about 250rpm) and the temperature is raised to 80±1℃. After the temperature stabilizes, about 10% of the APS solution (i.e., 0.2 parts of APS dissolved in 2 parts of water) is quickly injected to initiate the reaction. The reaction is maintained at this temperature for about 15-20 minutes. After the system shows a "blue phase", stirring is continued at 80℃ for 30 minutes to form a stable seed emulsion. Maintaining a temperature of 80℃, the remaining pre-emulsion and the remaining APS aqueous solution (1.8 parts APS dissolved in 18 parts water) are added dropwise to the seed emulsion at a uniform rate over 2.0 hours. After the addition is complete, the temperature is raised to 90±1℃ and maintained for 1 hour. After the reaction solution cools naturally to below 40℃, ammonia water is slowly added dropwise to adjust the pH to 7.0-7.5. Finally, the solution is filtered through a 300-mesh nylon filter cloth to obtain a milky white water-based acrylic resin emulsion with a solid content of approximately 38-40%, labeled A1, and stored in a sealed container.

[0045] Comparative Example 1: Preparation of PDMS-free acrylic resin emulsion (D1) The preparation method of this comparative example is exactly the same as that of Example 2, except that K-PDMS is not added in the pre-emulsification stage, and the amount of MMA is increased from 70 parts to 75 parts to keep the total monomer content unchanged. The resulting emulsion is denoted as D1.

[0046] Comparative Example 2: Preparation of Emulsion (D2) Containing Physically Mixed Unmodified PDMS The preparation method of this comparative example is basically the same as that of Example 2, except that 5 parts of K-PDMS were replaced with 5 parts of unmodified hydroxyl-terminated PDMS (the same raw materials as in Example 1) during the pre-emulsification stage. During the preparation process, emulsification was slightly difficult, and the resulting emulsion was designated as D2. After standing for 24 hours, a small amount of oily substance was precipitated at the bottom.

[0047] Example 3: Formulation and Coating Performance Testing of Water-Based Peelable Coatings This embodiment illustrates the formulation of coatings and the systematic testing of coating performance.

[0048] First, according to the formula in Table 1 below, prepare coatings using emulsions A1, D1, and D2 respectively. During preparation, add each component to the beaker in sequence, stirring at 500-800 rpm for 2-3 minutes until homogeneous after each addition. After all components are added, disperse at 1500 rpm for 10-15 minutes, allow to stand to defoam for 1 hour, and then use. The resulting coatings are designated P-A1, P-D1, and P-D2 respectively.

[0049] Table 1: Formulations of water-based peelable coatings (parts by weight) Components Model / Description Dosage (servings) Waterborne acrylic resin emulsions (A1, D1, or D2) - 70 Deionized water - 24 wetting agent BYK-346 0.3 Defoamer TEGO Foamex 810 0.2 Leveling agent TEGO Glide 450 0.2 Thickener ASE-60 (2% aqueous solution) 5.0 (equivalent to 0.1 parts solid) dispersant TEGO Dispers 750W 0.3 Pigment Phthalocyanine Blue Water-based Pigment (50% Solids) 2 total Approximately 102.0 The coating preparation process is as follows: A float glass plate (150mm × 70mm × 3mm) was cleaned and dried with acetone and anhydrous ethanol. The coating was evenly applied to the glass plate using a 100μm wet film preparation device, and then baked in an 80℃ forced-air drying oven for 20 minutes. After cooling, the dry film thickness was approximately 40-50μm. At least three parallel samples were prepared for each coating.

[0050] All performance tests were conducted in a standard environment of 23±2℃ and 50±5% relative humidity, with the samples conditioned for at least 24 hours before testing. The test results were averaged and summarized in Table 2 below.

[0051] Table 2: Results of Comprehensive Coating Performance Tests As shown in Table 2, the coating P-A1 prepared using the method of this invention exhibits superior peelability, mechanical strength, hydrophobicity, and heat resistance compared to the control samples. The P-A1 coating demonstrates the best appearance, proving that K-PDMS achieves good compatibility with acrylic resin through chemical copolymerization. In contrast, the appearance defects of P-D2 directly reflect the phase separation problem caused by the unmodified PDMS through physical mixing. P-A1 exhibits an ideal state of "easy initiation and continuous, complete peeling," thanks to the uniform and moderate interfacial adhesion provided by chemically bonded PDMS and the coating's own high toughness (high tensile strength and elongation at break). P-D1, lacking the lubrication and toughening effect of PDMS, is brittle and prone to fracture. P-D2 suffers from uneven interfacial bonding due to phase separation, resulting in the worst peel performance. The tensile strength (13.46 MPa) and elongation at break (185%) of P-A1 are significantly higher than both control samples, demonstrating the toughening and strengthening effect of chemically bonded PDMS on the acrylic resin network. The extremely high contact angle (102.6°) of P-A1 demonstrates the effective enrichment of PDMS segments on the surface, resulting in excellent hydrophobicity. Its highest thermal decomposition temperature (262℃) and good short-term heat resistance performance verify that chemically bonded PDMS significantly improves the thermal stability of the coating. The various performance defects of comparative examples D1 and D2, in turn, confirm the necessity and outstanding effect of the present invention's technique of "chemically modifying PDMS and participating in copolymerization."

[0052] Example 4: Application of glass mold demolding This embodiment simulates a real-world application scenario to verify the practicality of the coating of the present invention in the demolding of glass molds.

[0053] A semi-cylindrical concave transparent glass mold (radius of curvature R = 100 mm) was selected. Following the method in Example 3, the clean inner surface of the mold was uniformly sprayed with coating P-A1 (wet film thickness approximately 80 μm), and dried at 80°C for 30 minutes to form a peelable coating with a dry film thickness of approximately 50 μm. Three layers of pre-impregnated epoxy resin carbon fiber fabric (prepreg) were manually laid on this coating to simulate the composite material layup process. The entire system was then placed in an autoclave and cured according to the following procedure: the temperature was increased from room temperature to 120°C at a rate of 2°C / min, held at 120°C under pressure (0.6 MPa) for 2 hours, and then cooled in the autoclave to below 60°C before removal.

[0054] After cooling, a corner of the coating is gently pried off from the mold edge using a plastic scraper. Because the adhesion between the coating and the cured carbon fiber composite product surface is slightly greater than its adhesion to the glass mold, and because the coating itself has high strength, the operator can very smoothly peel the entire "cured product + peelable coating" as a whole off the glass mold. The inner surface of the glass mold after peeling is smooth and clean, without any coating or resin residue. The peeled coating remains largely intact, adhering to the back of the product, and can be easily peeled off as needed. This application example fully demonstrates the effectiveness, reliability, and convenience of the coating of this invention in the actual glass mold demolding process.

[0055] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a water-based, environmentally friendly, peelable coating for a glass substrate, characterized in that, Includes the following steps: (1) Preparation of modified polydimethylsiloxane K-PDMS: Polydimethylsiloxane PDMS is reacted with a silane coupling agent in the presence of a solvent and a catalyst. After removing the solvent, K-PDMS with reactive double bonds is obtained. (2) Preparation of preemulsion: Mix emulsifier, acrylate monomer, K-PDMS obtained in step (1) and deionized water, and stir evenly to obtain preemulsion; (3) Preparation of seed emulsion: Add a portion of the pre-emulsion to a reaction vessel containing buffer and deionized water, heat to 75-85°C, add a portion of initiator solution to initiate, and keep warm after the system shows a blue phase to obtain seed emulsion; (4) Emulsion polymerization reaction: The remaining pre-emulsion and the remaining initiator solution are added dropwise to the seed emulsion at the same time. After the addition is completed, the temperature is raised to 85-95℃ and kept warm for maturation to obtain a polymerized emulsion. (5) Emulsion post-treatment: Cool the polymer emulsion obtained in step (4), adjust the pH value to 6-8, filter, and obtain an aqueous acrylic resin emulsion. (6) Coating preparation: The water-based acrylic resin emulsion obtained in step (5) is mixed with deionized water, additives and color paste to prepare a water-based environmentally friendly peelable coating.

2. The preparation method according to claim 1, characterized in that, In step (1), the silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane (KH550), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), and γ-(methacryloyloxy)propyltrimethoxysilane (KH570); the solvent is 2-methyltetrahydrofuran; and the catalyst is dibutyltin dilaurate.

3. The preparation method according to claim 1, characterized in that, In step (2), the amount of acrylate monomers used is 80-100 parts by mass, the amount of K-PDMS used is 1-10 parts, and the amount of emulsifier used is 3%-5% of the total mass of acrylate monomers and K-PDMS.

4. The preparation method according to claim 3, characterized in that, The acrylate monomers include hard monomers and functional monomers; the hard monomers are selected from at least one of methyl methacrylate and styrene; the functional monomers are selected from at least one of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, and butyl acrylate.

5. The preparation method according to claim 1 or 3, characterized in that, In step (2), the emulsifier is a compound system of nonionic emulsifier and anionic emulsifier; the nonionic emulsifier is selected from alkylphenol polyoxyethylene ether (OP-10); the anionic emulsifier is selected from at least one of sodium dodecyl sulfate (SDS) and sodium diisooctyl sulfosuccinate.

6. The preparation method according to claim 1, characterized in that, In step (3), the buffer is sodium bicarbonate; the initiator solution is an aqueous solution of ammonium persulfate and potassium persulfate.

7. The preparation method according to claim 1, characterized in that, In step (3), the amount of the pre-emulsion is 40%-60% of the total amount of the pre-emulsion; the amount of the initiator is 5%-10% of the total mass of the initiator.

8. The preparation method according to claim 1, characterized in that, In step (5), ammonia or organic amines are used as pH adjusters.

9. The preparation method according to claim 1, characterized in that, In step (6), the additives include at least two of the following: defoamer, wetting agent, leveling agent, thickener and dispersant; the amount of the waterborne acrylic resin emulsion is 60-80 parts by mass.

10. A water-based, environmentally friendly, peelable coating, characterized in that, The aqueous acrylic resin emulsion prepared by any one of claims 1-9 is mixed with deionized water, additives, and color paste.

Citation Information

Patent Citations

  • Demolding surface material for composite parts

    CN108472920B

Cited By

  • A silicone aerosol type coating for waterproofing precision instruments and a method for preparing the same

    CN122278290A